The architecture of bridge design - Bennett, David (Thomas Telford, 1994)
At its best, a great bridge can satisfy the need for movement and delight the eye in a fusion of utility and beauty. At its worst, it can be brutally unimaginative and a permanent irritant to the aesthetic feelings of those that use it. These conference papers from 1994 discuss the issues.